THE INVESTIGATION OF THE KEY DETERMINANTS OF BEHAVIOUR OF PASSENGERS PURCHASING TICKETS VIA ONLINE PORTALS AND AUTOMATED TICKET VENDING MACHINES - Vashisth, Renu; Gupta, Jyoti (The journal of contemporary issues in business and government, 2022)
India has the 2nd fastest growing travel market globally. Of this, the online travel market is growing at the highest pace. In recent years, Indian Government has taken useful steps in this field. They have introduced IRCTC, online portal for ticket purchasing. Also following the trends of other countries India railway has installed several ATVM in the major stations to introduce digitalization for buying local tickets. As digitalization is trying to implement everywhere, but due to different factors some segment of people are not able to cop-up with this modernization. Also, to increase the use of plastic money and e-wallet these digitalized systems should be adapted quickly. So, the primary focus of this research is to evaluate the factors that influence/restrain the consumer behavior for online ticket purchasing & using ATVM for ticket purchasing in India, thus in the following sections we evaluate the Indian scenario related to it. To determine the factors, some market research has been done. For that, questionnaire has been prepared and sample has been selected.